Turkish version of the Massachusetts General Hospital Cognitive and Physical Functioning Questionnaire: A reliability and validity study - Mehmet Alptekin Karaçeşme,; Manolya İlhanlı,; İlker İlhanlı, (Archives of Rheumatology, 2024)
Objectives: This study aimed to analyze the validity and reliability of the Turkish version of the Massachusetts General Hospital Cognitive and Physical Functioning Questionnaire (CPFQ) in patients with fibromyalgia (FM) syndrome by translating and culturally adapting the CPFQ to Turkish. Patients and methods: One hundred seventeen patients (8 males, 109 females; mean age: 47.4±12.4 years; range, 18 to 77 years) diagnosed with FM according to the 2016 American College of Rheumatology FM diagnostic criteria between May 2021 and August 2021 were included in the reliability and validity study. The CPFQ was translated into Turkish, the intelligibility of the obtained Turkish version was evaluated by five patients and five healthcare professionals, and the final form of the questionnaire was prepared. Mini-mental state examination (MMSE), Fibromyalgia Impact Questionnaire (FIQ), and Hospital Anxiety and Depression Scale (HADS), which were proven to be reliable and valid in Turkish, were administered to the patients. For test-retest reliability, the Turkish version of the CPFQ was filled in two times with an interval of one week. Internal consistency was evaluated by calculating Cronbach's alpha. Validity was evaluated by looking at the correlations between the total score obtained from the Turkish version of CPFQ and the MMSE score, HADS depression and anxiety scores, and FIQ score. Results: In the evaluation of internal consistency, Cronbach's alpha was found to be high in all subgroups. In test-retest reliability, intraclass correlation coefficient was high in CPFQ subgroups. The CPFQ showed a significant positive correlation with HADS depression and a moderately positive correlation with HADS anxiety and FIQ. A significant but weak negative correlation was detected between CPFQ and MMSE. While there was no significant correlation between MMSE and FM disease activity and HADS anxiety, there was a significant but weak negative correlation between HADS depression. Conclusion: In this study, the Turkish version of CPFQ was shown to have high reliability and validity in FM patients. It was concluded that CPFQ could be applied to Turkish patients with FM.